1990
DOI: 10.1007/bf00053670
|View full text |Cite
|
Sign up to set email alerts
|

Mid-chain ketocarboxylic acids in the remote marine atmosphere: Distribution patterns and possible formation mechanisms

Abstract: In remote marine aerosol samples collected from the North Pacific ocean, Enewetak Atoll, American Samoa, and New Zealand, series of mid-chain ketocarboxylic acids in the range of C 6-C1s were detected. All the positional isomers, except for the 2-oxo and 3-oxo species, were detected for major ketoaeid families (e.g. C 9 , C H and C13 ). Higher ketoacid concentrations (up to 19 ng/m 3 ) were obtained in the northern North Pacific aerosol samples, which generally showed an odd carbon-numbered predominance with 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 20 publications
2
32
1
Order By: Relevance
“…These two components account for 90% of the variance in the data sets, with 52% accounted for by the first component and 38% accounted for by the second component. The results in Table 2 suggest that the diacid distributions can be explained by a 100 , , , i , , , I , , , i , , , i , [Kawamura and Gagosian, 1990]. They are produced in the marine atmosphere by photochemical oxidation of semivolatile fatty acids which are counterpart of oxidative degradation of unsaturated fatty acids (see Figure 8a).…”
Section: Principal Component Analysis Of Diacid Datamentioning
confidence: 96%
“…These two components account for 90% of the variance in the data sets, with 52% accounted for by the first component and 38% accounted for by the second component. The results in Table 2 suggest that the diacid distributions can be explained by a 100 , , , i , , , I , , , i , , , i , [Kawamura and Gagosian, 1990]. They are produced in the marine atmosphere by photochemical oxidation of semivolatile fatty acids which are counterpart of oxidative degradation of unsaturated fatty acids (see Figure 8a).…”
Section: Principal Component Analysis Of Diacid Datamentioning
confidence: 96%
“…Strong anti-correlations between the relative abundance of oxalic acid to total n-saturated dicarboxylic acids (C 2 -C 10 ) and some high carbon number dicarboxylic acids [methylmalonic (iC 4 ), maleic (M), methylmaleic (mM), methylsuccinic (iC 5 ), adipic (C 6 ) and phthalic (Ph)], ketocarboxylic acids [glyoxylic (ωC 2 ) and pyruvic (Pyr)], and dicarbonyl [glyoxal (Gly)] have been reported in summer aerosols collected from urban Tokyo (Kawamura and Yasui, 2005). These authors also suggested that longer-chain (C 5 -C 10 ) dicarboxylic acids were produced through the oxidation of semi-volatile fatty acids (Kawamura and Gagosian, 1990;Kawamura et al, 1996a), which are also the oxidation products of unsaturated fatty acids that are abundant in leaves of higher terrestrial plants and are also emitted from wood burning (Rogge et al, 1998).…”
Section: Chemical Degradation Of Dicarboxylic Acids Ketocarboxylic Amentioning
confidence: 99%
“…The concentrations of 49 organic compounds in aerosol over the western Atlantic Ocean have been identified, and most of the species that were detected are long-chain insoluble species [Duce et al, 1983]. More polar substances, including dicarboxylic and ketocarboxylic acids, have also been identified in marine aerosol in the Pacific Ocean [Kawamura and Gagosian, 1990]. $axena and Hildemann [1996] postulate that a significant part of the unidentified organic aerosol mass consists of watersoluble polar species.…”
Section: Chemical Composition Of Sea Saltmentioning
confidence: 99%